2023
DOI: 10.1029/2022ms003482
|View full text |Cite
|
Sign up to set email alerts
|

Toward Eliminating the Decades‐Old “Too Zonal and Too Equatorward” Storm‐Track Bias in Climate Models

Abstract: This page was generated automatically upon download from the ETH Zurich Research Collection. For more information, please consult the Terms of use. tions of regional land surface climate" (WG1 Chapter 10). For the projection of future regional land precipitation changes downstream of the North Atlantic storm tracks, this implies increased uncertainty, since regional precipitation changes are mainly determined by large-scale circulation changes. As a result, the sign of, for example, changes in fall but also an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
(97 reference statements)
1
11
0
Order By: Relevance
“…The poleward shift of storm tracks with higher resolution is also found in other models (Schemm, 2023; Sein et al., 2018; Willison et al., 2013). Their findings suggested that better resolved diabatic processes may enhance the poleward propagation of extratropical cyclones (Coronel et al., 2015; Tamarin & Kaspi, 2017) and emphasized the impact of increasing atmospheric resolution (e.g., see Figure 8 in Sein et al., 2018).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The poleward shift of storm tracks with higher resolution is also found in other models (Schemm, 2023; Sein et al., 2018; Willison et al., 2013). Their findings suggested that better resolved diabatic processes may enhance the poleward propagation of extratropical cyclones (Coronel et al., 2015; Tamarin & Kaspi, 2017) and emphasized the impact of increasing atmospheric resolution (e.g., see Figure 8 in Sein et al., 2018).…”
Section: Resultssupporting
confidence: 80%
“…Over the North Atlantic, the storm track in LR is too weak over the Nordic Seas region, Europe, and the regions adjacent to the Grand Banks (by 14-18 gpm) compared to ERA5. As mentioned before, previous studies reported a too-zonal bias of the North Atlantic storm track with an overestimation over Europe and an underestimation over the Nordic Seas region (e.g., Harvey et al, 2020;Schemm, 2023). HR reduces the negative bias over Europe and the Nordic Seas region (of up to 9-13 gpm).…”
Section: Long-term Mean Boreal Winter Storm Trackmentioning
confidence: 64%
See 2 more Smart Citations
“…Storm resolving model data is now becoming regionally available, for example over Europe through CORDEX FPS convection (Coppola et al, 2020) or for the Lake Victoria area through CORDEX FPS Lake Victoria (van Lipzig et al, 2023), and globally in the next years through the digital twin developed within the Destination Earth project (Hoffmann et al, 2023). A few examples for processes where storm resolving simulations bring demonstrated benefit are the dynamics of the North Atlantic jet (Schemm, 2023), precipitation in complex orography (Ban et al, 2021), convection and circulation over Lake Victoria (Van de Walle et al, 2020), local features around islands in the Caribbean (Martinez et al, 2024), the subtropical Atlantic (Gao et al, 2023) and modeling lake-effect snow around the Tibetan Plateau (Lin et al, 2023). Higher resolution models, particularly for the ocean, have also been shown to have more fidelity in capturing SST trends than lower resolution models (Yeager et al, 2023).…”
Section: Leverage Tools To Understand Model-observation Discrepancies...mentioning
confidence: 99%